Haematological, biochemical and histopathological aspects of Hericium erinaceus ingestion in a rodent model: A sub-chronic toxicological assessment - Lakshmanan, H.; Raman, J.; David, P.; Wong, K.H.; Naidu, M.; Sabaratnam, V. (Elsevier, 2016)
Ethnopharmacological relevance Hericium erinaceus is a culinary-medicinal mushroom and has a long history of usage in traditional Chinese medicine as a tonic for stomach disorders, ulcers and gastrointestinal ailments. Aim of the study The present investigation was aimed to evaluate the potential toxic effects of the aqueous extract from the fruiting bodies of H. erinaceus in rats by a sub-chronic oral toxicity study. Materials and methods In this sub-chronic toxicity study, rats were orally administered with the aqueous extract of H. erinaceus (HEAE) at doses of 250, 500 and 1000 mg/kg body weight (b.w.) for 90 days. Body weights were recorded on a weekly basis and general behavioural changes were observed. The blood samples were subjected to haematological, biochemical, serum electrolyte, and antioxidant enzyme estimations. The rats were sacrificed and organs were processed and examined for histopathological changes. Results No mortality or morbidity was observed in all the treated and control rats. The results showed that the oral administration of HEAE daily at three different doses for 90 days had no adverse effect on the general behaviour, body weight, haematology, clinical biochemistry, and relative organ weights. Histopathological examination at the end of the study showed normal architecture except for few non-treatment related histopathological changes observed in liver, heart and spleen. Conclusion The results of this sub-chronic toxicity study provides evidence that oral administration of HEAE is safe up to 1000 mg/kg and H. erinaceus consumption is relatively non-toxic.